2014
DOI: 10.1007/s13668-014-0082-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, Clock Genes, and Chrononutrition

Abstract: Circadian clocks that comprise clock genes exist throughout the body and control daily physiological events. The central clock that dominates activity rhythms is entrained by light/dark cycles, whereas peripheral clocks regulating local metabolic rhythms are determined by feeding/fasting cycles. Nutrients reset peripheral circadian clocks and the local clock genes control downstream metabolic processes. Metabolic states also affect the clockworks in feedback manners. Because the circadian system organizes whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 99 publications
2
119
0
8
Order By: Relevance
“…Control of ribosome biogenesis and mitochondrial function by the circadian clock and feeding rhythms could therefore provide key factors in pathologies associated with circadian disruption. In this way, the concept of chrononutrition, in the sense of synchronizing feeding rhythms to the circadian clock-imposed rhythmic metabolism, acquires a mechanistic basis and could lead to nonpharmacological strategies to prevent metabolic diseases (74).…”
Section: Consequence Of Desynchronized Circadian Clock and Feeding Rhmentioning
confidence: 99%
“…Control of ribosome biogenesis and mitochondrial function by the circadian clock and feeding rhythms could therefore provide key factors in pathologies associated with circadian disruption. In this way, the concept of chrononutrition, in the sense of synchronizing feeding rhythms to the circadian clock-imposed rhythmic metabolism, acquires a mechanistic basis and could lead to nonpharmacological strategies to prevent metabolic diseases (74).…”
Section: Consequence Of Desynchronized Circadian Clock and Feeding Rhmentioning
confidence: 99%
“…Circadian clocks and energy metabolism interact and nutritional outcomes are affected by the timing of food intake even when the same type of food and the same amount of calories are consumed [1,[5][6][7][8]. For example, time-restricted feeding without reducing caloric intake suppresses obesity induced by a high fat diet [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…134 It has been suggested that postprandial glycemia is under circadian regulation and that its misalignment may lead to glucose intolerance. 130 Eating late during the day was associated with decreased resting-energy expenditure, decreased fasting carbohydrate oxidation, decreased glucose tolerance, blunted daily profile in free cortisol concentrations and decreased thermal effect of food on wrist temperature in normal weight, healthy females.…”
Section: Meal Frequency Meal Timing and Pcosmentioning
confidence: 99%